INVESTIGATION LEGALITY AND CERTIFICATION PROCESS OF HALAL PRODUCT GUARANTEE: South Korea Muslim Federation as a Muslim Minority Country - Chanifah, Nur; Rohmah, Siti; Kholish, Moh. Anas; Syaikhoni, Syaikhoni; Samsudin, Abu; Ansori, Ibnu Hajar (Al-Risalah, 2025)
The halal industry is getting attention all over the world, including in countries with Muslim minorities such as South Korea. This country is committed to increasing tourism and promoting halal products, as evidenced by the issuance of a halal certification by the Korea Muslim Federation (KMF). This study examines the laws and procedures governing halal certification in South Korea, a secular country. A qualitative phenomenological approach was employed in this study, involving in-depth interviews with the president and administrators of KMF, as well as observations of halal products and restaurants. The study reveals that the South Korean government is collaborating with KMF for halal certification; however, limited human resources pose a significant obstacle. To overcome this, KMF is cooperating with Muslim-majority countries. In addition, a separate challenge is Korean culture, which is unfamiliar and often conflicts with Islam. Therefore, it is recommended that the government and KMF be more active in socializing the halal concept through exhibitions and public education. This effort is crucial to increasing public acceptance and supporting the success of South Korea's halal certification policy.